Penegakan Hukum Jasa Titip (Jastip) Tiket Konser Melalui Website Ilegal Dalam Perspektif Hukum Perlindungan Konsumen - Huwaida, Nisrina; Budi Setianingrum, Reni (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2024)
Law enforcement related to concert ticket entrustment services through illegal websites in the perspective of consumer protection law is an important issue in the realm of consumer law. Cases of fraud in the sale of illegal concert ticketing services are being investigated by the authorities, and criminal sanctions can be given to the business actors involved. Legal protection for consumers who have been harmed is also regulated in Law Number 8 of 1999 concerning Consumer Protection, which provides legal consequences for business actors who do not fulfill their obligations, including fines and penalties. In addition, legal protection of consumers also involves coordination with relevant agencies, the delivery of information to increase consumer awareness, and consumer support in fighting for their rights. Therefore, law enforcement in the case of illegal concert ticketing services through the website involves criminal sanctions, legal protection of consumers, and efforts to increase consumer awareness